Anthropomorphism – matters or not? On agent modality and its implications for teaching English idioms and design decisions. Issue 1 (17th February 2017) - Ahmadi, Alireza; Sahragard, Rahman; Babaie Shalmani, Hamed
ABSTRACT: The present study aimed to examine whether agent-based instruction would privilege English as a Foreign Language (EFL) learners any better than mainstream approaches (e.g. analogical reasoning, guessing from context, image formation, semantic analysis, etc.) when it comes to the teaching of English idioms. It also sought to explore whether learning from multimedia agents and retention of English idioms would be differentially impacted if agent modality were concerned. To this end, three constellations of EFL learners, each consisting of 30 participants, received instruction on 128 English idioms under one of three conditions: One group received treatment through an anthropomorphic pedagogical agent that was capable of coordinating speech with a diverse range of human paralinguistic behaviors. Another group received treatment on the target idioms through a non-anthropomorphic agent in the form of an animated hand with a pointing finger that was capable of showing a small subset of human non-verbal behaviors. The other group received treatment on English idioms the conventional way, that is, through teacher-fronted instruction. The findings revealed that the participants learned better from agent-based instruction and that the pointing finger had proved even more efficient in teaching English idioms.